Cross-platform data integration of paratubal electromyography and sonotubometry for eustachian tube: a pilot study. (1st November 2016) - Lin, Chenxi; Li, Yanning; Lin, Xin; Zhang, Shaohua; Tang, Anzhou; Nong, Dongxiao
Abstract: Conclusion: The sensitive sonotubometry and MATLAB provide a new tool to study the eustachian tube (ET) function and contribute more to reliable data and precise analysis. The levator veli palatini muscle (mLVP) and the salpingopharyngeus muscle (mSP) may, respectively, be the most important and least important muscle for ET function. Objectives: The ET lumen dilation is a result of the contraction of the paratubal muscles, the tensor veli palatini muscle (mTVP), mLVP and mSP. To trace the dynamic ET muscle/lumen activities, the present study aimed to optimize sonotubometry and achieve cross-platform data integration of electromyography (EMG) and sonotubometry using MATLAB (matrix laboratory). Method: Seventeen healthy volunteers (34 ears) were chosen for the concurrent recordings of the paratubal EMG and sonotubogram under dry and water swallowing. Results: The optimized sonotubometry based on computer sound card showed satisfied sensitivity. For both EMGs and sonotubogram, dry swallowing generated significantly greater amplitude and longer duration compared to water swallowing. Moreover, statistically significant differences ( p  < 0.05) were detected in the comparison of the amplitude, duration, and latency for the mTVP, mLVP, and mSP. The mSP activity was the weakest and even inactive in some cases, the mLVP presented the most powerful and long lasting activity during ET-opening.